Nonseizure SUDEP: Sudden unexpected death in epilepsy without preceding epileptic seizures. (25th May 2016) - Lhatoo, Samden D.; Nei, Maromi; Raghavan, Manoj; Sperling, Michael; Zonjy, Bilal; Lacuey, Nuria; Devinsky, Orrin
Summary: Objective: To describe the phenomenology of monitored sudden unexpected death in epilepsy (SUDEP) occurring in the interictal period where death occurs without a seizure preceding it. Methods: We report a case series of monitored definite and probable SUDEP where no electroclinical evidence of underlying seizures was found preceding death. Results: Three patients (two definite and one probable) had SUDEP. They had a typical high SUDEP risk profile with longstanding intractable epilepsy and frequent generalized tonic–clonic seizures (GTCS). All patients had varying patterns of respiratory and bradyarrhythmic cardiac dysfunction with profound electroencephalography (EEG) suppression. In two patients, patterns of cardiorespiratory failure were similar to those seen in some patients in the Mortality in Epilepsy Monitoring Units Study (MORTEMUS). Significance: SUDEP almost always occur postictally, after GTCS and less commonly after a partial seizure. Monitored SUDEP or near‐SUDEP cases without a seizure have not yet been reported in literature. When nonmonitored SUDEP occurs in an ambulatory setting without an overt seizure, the absence of EEG information prevents the exclusion of a subtle seizure. These cases confirm the existence of nonseizure SUDEP; such deaths may not be prevented by seizure detection–based devices. SUDEP risk in patients with epilepsy may constitute a spectrum of susceptibility wherein some are relatively immune, death occurs in others with frequent GTCS with one episode of seizure ultimately proving fatal, while in others still, death may occur even in the absence of a seizure. We emphasize the heterogeneity of SUDEP phenomena.